Effect of the cooperative learning strategy on the learning of the soccer throw-in in university students - Hadi AlAridhee, Waleed Sameer; Hussein Kahat, Thamer; Mohammed Abdallah , Wathik (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The present research aimed to study the effect of the cooperative learning strategy on the learning of the soccer throw-in in university students. The research sample included 22 first-year students of the College of Physical Education and Sports Sciences of the University of Al-Qadisiyah. The 22 students were divided into two experimental groups, with 11 students in each group. The first experimental group received only teaching through cooperative learning strategy. The second experimental group received not only teaching through cooperative learning strategy, but also the use of the soccer throw-in device guided by the teachers. The statistical analyses were carried out with the Statistical Package for Social Sciences (SPSS). The cooperative learning strategy significantly improved the soccer throw-in in university students. The improvement was higher when the cooperative learning strategy was combined with the use of the soccer throw-in device. Considering these results, the authors recommend to combine the cooperative learning strategy with the use of the soccer throw-in device to teach the soccer throw-in in university students.